Implementation Of "Program Sekolah Penggerak" In the Independent Learning Policy - Mawaddah Islamiyah, Nur; Nurochim, Nurochim; Syukur, Muhammad (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
This study aims to determine the Implementation of the Sekolah Penggerak Program in the Independent Learning Education Policy at SDN 28 Malay, Bima City. This research uses a qualitative descriptive approach. The data collection technique is by observation, namely, to see the implementation process in the field in the form of actions, interviews, namely, to obtain information in the form of words, and documentation, namely, to obtain data in the form of photos of activities and archives of the implementation of the Sekolah Penggerak program. The result of the study was that five interventions programmed by the government carried out the implementation of Sekolah Penggerak. Learning the intervention with a new paradigm, the school chose the theme of local wisdom and entrepreneurship, which became the first-year project. This theme entered into local content lessons; this intervention was carried out in extracurricular activities and positive culture. Meanwhile, in the school digitization intervention, using the PMM application, Google Classroom, Google Meet, zoom, Google, YouTube, learning videos, and digital libraries, as well as Quiziz applications and Google forms as a medium for assessment.